Oral rehabilitation of the cancer patient: A formidable challenge. Issue 8 (3rd May 2018) - Petrovic, Ivana; Rosen, Evan B.; Matros, Evan; Huryn, Joseph M.; Shah, Jatin P.
Abstract : Rehabilitation of oral functions following surgery on the jaws is a goal that is often difficult to achieve. Removable dentures supported by remaining teeth or gum are often unstable and seldom satisfactory. On the other hand, endosseous (dental) implants offer a mechanism to provide stability to the dentures. This review, discusses factors related to the tumor, patient, treatment, and physicians which impact upon the feasibility and success of dental implants in patients with oral cancer.